(untitled) (Lex localis - Journal of Local Self-Government, 2022)
The use of public-private partnerships (PPPs) for infrastructure development can alleviate the high levels of government debt associated with these projects while encouraging new investment as well. We developed a theoretical analysis of infrastructure projects and the applicability of PPPs. Next, we provided an empirical analysis based on statistics from the PPP database of the Ministry of Finance from 2013 to 2017. Based on our results, this paper offers reasonable and effective guidance for restructuring China’s PPP governance to improve the participation of government departments, the private sector, and the public in PPPs for infrastructure development.